Frank O. Etheridge : jazz musician of the African diaspora - Etheridge, Frank O., 1897-1967; Vinson, Ben, III (Abingdon, Oxon ; New York : Routledge, 2024)
"This is a book by and about Frank O. Etheridge, an African-American musician from an age of cultural explosion. This manuscript, published for the first time, will be accompanied by editorial commentary written by Professor Ben Vinson III, and will be of great interest to students and scholars of African American history"--
Introduction -- A story in black and white : a musical travelogue -- What ever became of race prejudice? -- People and places.
Keywords: Etheridge, Frank O., -- 1897-1967.; Etheridge, Frank O., -- 1897-1967 -- Travel; Jazz musicians -- United States; African American jazz musicians; Race discrimination -- United States; Music and race -- United States; HISTORY / Modern / 20th Century; HISTORY / Social History